Privātpersonu kreditēšana Komercbankās - Stepanovs, Jurijs (Latvijas Universitāte, 2007)
Magistra darba temats - “Privatpersonu kreditesana komercbankas”. Magistra darba butibu izskaidro ekonomiski pamatota privatsektora pastavigi augosa pieprasijuma apmierinasanai finansu resursu trukums, kas nosaka stabilu augsta limena pieprasijumu uz ekonomisko subjektu dalas briviem lidzekliem, kurus vini ir gatavi piegadat uz noteiktu terminu par noteiktu maksu. Piedavata darba merkis - privatpersonu kreditesanas tirgus komercbankas petisana un analize, vajo momentu definesana un iedzivotaju kreditesanas sistemas dazu problemu risinasanas iespeju izstrade. Magistra darba petijumu rezultata tika izskatita un izanalizeta privatpersonu kreditesanas sociali ekonomiska nozime, piedavati kreditesanas attistibas risinajumi privatpersonam dzives apstaklu uzlabosanai, ka ari izskatitas izglitibas ieguves perspektivas ar kreditesanas palidzibu.

The theme offered in magister’s work is "Crediting of private persons in commercial banks". The essence of magister work is explained by the economically proved shortage of financial resources for the satisfaction of a constantly growing demand of a private sector causes a stable high level of demand on available assets of the certain part of economic subjects, which are ready to extend monetary assets for the certain term, for the certain payment. The purpose of the offered work is studying and the analysis of features of development of the market of crediting of private persons in commercial banks, revealing of weaknesses of process and development of possible variants of the decision of some problems in the system of crediting of the population. As a result of researches have been considered and analysed socially economic value of crediting of private persons. Decisions on development of crediting of private persons for improvement of living conditions are offered. The prospects of crediting for reception of formation are considered.
Crediting of Private Persons in Commercial Banks
Keywords: Ekonomika